Grip type and task goal modify reach-to-grasp performance in post-stroke hemiparesis - Schaefer, Sydney Y. (2012)
This study investigated whether grip type and/or task goal influenced reaching and grasping performance in post-stroke hemiparesis. Sixteen adults with post-stroke hemiparesis and twelve healthy adults reached to and grasped a cylindrical object using one of two grip types (3-finger or palmar) to achieve one of two task goals (hold or lift). Performance of the stroke group was characteristic of hemiparetic limb movement during reach-to-grasp, with more curved handpaths and slower velocities compared to the control group. These effects were present regardless of grip type or task goal. Other measures of reaching (reach time and reach velocity at object contact) and grasping (peak thumb-index finger aperture during the reach and peak grip force during the grasp) were differentially affected by grip type, task goal, or both, despite the presence of hemiparesis, providing new evidence that changes in motor patterns after stroke may occur to compensate for stroke-related motor impairment.